Perinuclear Antineutrophil Cytoplasmic Antibodies in Collagenous or Lymphocytic Colitis with or without Celiac Disease - Hugh James Freeman (Canadian Journal of Gastroenterology)
Microscopic forms of colitis, including lymphocytic and collagenous colitis, have been observed in both those with and without celiac disease. Although perinuclear antineutrophil cytoplasmic antibodies (p-ANCA) occur in most patients with ulcerative colitis, investigations in microscopic, particularly lymphocytic, colitis are still needed. In this study atypical p-ANCA was evaluated in 55 patients, including 27 with celiac disease alone, 13 with celiac disease and concomitant lymphocytic colitis, and 15 with microscopic forms of colitis, including lymphocytic and collagenous colitis. Nine patients (16.3%) had atypical p-ANCA, including six with celiac disease and three with a microscopic form of colitis alone. Although five of the six positive celiac disease patients had lymphocytic colitis, all three celiac disease patients with associated primary sclerosing cholangitis - a separate risk factor for a positive assay result - were serologically positive for atypical p-ANCA. These results indicate for the first time that this serological marker may occur in histologically defined celiac disease with or without concomitant lymphocytic colitis. Furthermore, these results suggest that the pathogenesis of ulcerative colitis differs from that of lymphocytic colitis and further emphasizes the heterogeneous nature of these newly recognized types of colonic inflammatory mucosal disorders.